Imitation of the coinage of Æthelraed II in Central Europe - Suchodolski, Stanislaw (Hikuin, 1985)
It has long been known that Anglo-Saxon coins were imitated on the Continent, and research co-operation between Scandinavian and British scholars has provided us with ever more information on this subject. One of the most outstanding contributions in this field has been made by Brita Maimer, who by using new research methods as early as 1965 achieved very interesting results in her studies of the places and periods when Æthclraed H’s pennies were imitated in Swedish territories . On the basis of the die-links between the imitations and the official coinage of Olof Skotkonung struck in the mint at Sigtuna, she has shown that at least some of these imitations were produced at this mint. Our knowledge of Scandinavian imitation of Anglo-Saxon coins has been further extended by the papers of M. Blackburn, M. Dollcy and other scholars, published in the exceptionally useful volume, “Studies in Northern Coinages of the Eleventh Century” (København 1981).